OMBUDSMAN SEBAGAI LEMBAGA PENGAWAS PELAYANAN PUBLIK DI INDONESIA - Izzati, Nabila Firstia (SASI, 2020)
The Ombudsman of the Republic of Indonesia as an institution that helps to administer public services has an important role in the administration of effective and efficient public services. However, it is recognized that it still exists in the implementation of public service supervision. First, it still represents the Ombudsman of the Republic of Indonesia which cannot be transferred by the invited party because many consider that the ombudsman must be invited is not mandatory. Second, it is constrained by the absence of regulations related to Ombudsman approval and sanctions that must be applied. Third, there is no execution of punishment by the Government for the cancellation of public services to the Regional Head launched by the Indonesian Ombudsman. Both the government and the publik society should support the implementation of the supervision of public administration by the Ombudsman in order to create public welfare.The Ombudsman of the Republic of Indonesia as an institution that helps to administer public services has an important role in the administration of effective and efficient public services. However, it is recognized that it still exists in the implementation of public service supervision. First, it still represents the Ombudsman of the Republic of Indonesia which cannot be transferred by the invited party because many consider that the ombudsman must be invited is not mandatory. Second, it is constrained by the absence of regulations related to Ombudsman approval and sanctions that must be applied. Third, there is no execution of punishment by the Government for the cancellation of public services to the Regional Head launched by the Indonesian Ombudsman. Both the government and the publik society should support the implementation of the supervision of public administration by the Ombudsman in order to create public welfare.